KEPEMIMPINAN DAN PELAYANAN DALAM ORGANISASI PUBLIK - Fitriani, Laksmi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
Public service has always been an actual topic among citizens. It is sensible because, on one hand, citizens seem to be inescapable from public services; on the other hand, public services have yet to meet citizens? needs. There are several factors causing unsatisfactory public service delivery. Those include lowwelfare and poor work discipline among public service workers. Another influential factor is leadership. It is believed that good leadership escorts the public organizations to good management of resources, which eventually leads to good public services.